2010
DOI: 10.1051/0004-6361/200913550
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the merger-driven evolution of active galaxies using the CJF sample

Abstract: Context. For the evolution of large-scale structures in the Universe, it is unclear whether active galaxies represent a phase that each galaxy undergoes, and whether and to which extent the evolution of black holes at their centers is important. Binary black hole (BBH) systems may play a key role in our understanding of the above questions. Aims. We investigate the Caltech-Jodrell Bank flat-spectrum (CJF) sample to identify evidence that supports the merger-driven evolution scheme of active galaxies, and searc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 174 publications
0
20
0
Order By: Relevance
“…The connection to AGN activity predicted by simulations is supported by many studies that find high incidences of tidal features associated with AGNs (Treister et al 2012;Cotini et al 2013;Ellison et al 2013;Satyapal et al 2014;Rosario et al 2015), including Karouzos et al (2010), who found that nearly 30% of active galaxies showed signs of an interaction or merger in the optical and infrared. Nazaryan et al (2014) performed an optical study of 180 Markarian galaxy pairs and found that ongoing mergers are 7 times more likely to contain an AGN than interacting pairs.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…The connection to AGN activity predicted by simulations is supported by many studies that find high incidences of tidal features associated with AGNs (Treister et al 2012;Cotini et al 2013;Ellison et al 2013;Satyapal et al 2014;Rosario et al 2015), including Karouzos et al (2010), who found that nearly 30% of active galaxies showed signs of an interaction or merger in the optical and infrared. Nazaryan et al (2014) performed an optical study of 180 Markarian galaxy pairs and found that ongoing mergers are 7 times more likely to contain an AGN than interacting pairs.…”
Section: Introductionmentioning
confidence: 54%
“…In simulations, major encounters between similar mass (typically ≤4:1 mass ratio), gas-rich galaxies are predicted to drive gas to the centers of interacting and merging systems triggering new star formation (SF) and fueling an AGN (Volonteri et al 2003;Hopkins et al 2008;Di Matteo et al 2005;Debuhr et al 2011). Many observational studies support the correlation between AGNs and merging systems (Karouzos et al 2010;Treister et al 2012;Cotini et al 2013;Ellison et al 2013;Nazaryan et al 2014;Satyapal et al 2014;Rosario et al 2015). However, other researchers, particularly those working at shorter wavelengths, do not find such a connection (Cisternas et al 2011;Kocevski et al 2012;Fan et al 2014;Scott & Kaviraj 2014;Villforth et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The X-ray properties have been studied and correlated with their VLBI properties (Britzen et al 2007a). The evolution of active galaxies, in the context of the merger-driven evolution scheme (e.g., Hopkins et al 2006), was also investigated with the help of the CJF, identifying candidate CJF sources in different evolutionary stages, including new binary black hole candidates (Karouzos et al 2010). …”
Section: The Cjf Samplementioning
confidence: 99%
“…in the center of galaxies, now commonly referred to as a Active Galactic Nuclei (AGN), can be triggered in a variety of ways. Merger driven models (Hopkins et al 2008;Ramos Almeida et al 2010;Karouzos et al 2010;Sabater et al 2013), induce accretion by both disrupting existing cold gas reservoirs in the merging galaxies and via the direct inflow of gas from the merger event itself. Alternatively, there is evidence to support the triggering of AGN in non-merging galaxies (Crenshaw et al 2003, Schawinski et al 2014, Draper et al 2012 and references therein) via supernova winds, stellar bars and the efficient inflow of cold gas from the intergalactic medium.…”
mentioning
confidence: 99%